1991
DOI: 10.1002/jso.2930470102
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pulmonary metastasectomy for recurrent soft tissue sarcoma

Abstract: To evaluate surgical results of resection of second (recurrent) pulmonary metastases from adult soft tissue sarcoma, the survival of 39 patients was analyzed retrospectively. With the exclusion of two patients (one with interval metastases between staged resections and one without histologically proved metastases), three patients were found to have unresectable disease (median survival, 7 months). A significantly (P = 0.0001) longer median survival (28 months) was found for 34 patients whose recurrent metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
6

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 14 publications
(5 reference statements)
1
20
0
6
Order By: Relevance
“…Another variable found to be independently significant was the number of metastases. This accords with the study by Casson et al (1991) who also found that 2 or more pulmonary metastases were associated with a significant decrease in median survival. A study from the National Cancer Institute has also shown that the number of pulmonary nodules affected survival (Roth et al 1985).…”
Section: Discussionsupporting
confidence: 92%
“…Another variable found to be independently significant was the number of metastases. This accords with the study by Casson et al (1991) who also found that 2 or more pulmonary metastases were associated with a significant decrease in median survival. A study from the National Cancer Institute has also shown that the number of pulmonary nodules affected survival (Roth et al 1985).…”
Section: Discussionsupporting
confidence: 92%
“…There was one retrospective cohort study of data obtained from a Cancer Centre's institutional Tumor Registry 11. In other reports, cases were identified from databases which were held, as far as we could determine, at an institutional level10 12–17 20 23 26 27 or departmental level 18 19 21 24 25. It appears that many of the clinical data were retrieved by retrospective case note review.…”
Section: Resultsmentioning
confidence: 99%
“…In 10 of the 18 reports, statistical analyses were performed to identify patient and tumour characteristics associated with improved survival following first pulmonary metastasectomy 11 13 14 16 18 19 21 23 25 26…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metastectomy has a long history in the management of multiple tumors from other sites that have spread to the lungs, particularly late recurrences from primary sarcomas extirpated from other parts of the body. The natural history of metastatic sarcomas in the lung is terminal (1)(2)(3). Colorectal adenocarcinomas, which are far more common than sarcomas, commonly spread to the lungs and are often resected and chemotherapy is administered neoadjuvantly or adjuvantly.…”
Section: Multimodality Therapy For Pulmonary Soft Tissue Sarcomasmentioning
confidence: 99%